TEACHING GRAMMAR THROUGH VISUAL ILLUSTRATION FOR THE UNIVERSITY STUDENTS - Syafryadin Syafryadin (IKIP Siliwangi, 2021)
Teaching grammar needs to be developed by the lecturer or the teacher. The lecturer must find out an alternative way to build good atmosphere in teaching grammar. Hence, one of the alternative ways is through visual illustration. This study examined the visual illustration towards the students’ grammar ability enhancement and the problems of the students in learning grammar and the solution. This study combined quantitative and qualitative method in answering the research questions. The instruments are grammar test and interview guideline. The result showed that visual illustration technique is effective in teaching grammar for students. It can be proved by the result of simple statistic calculation, where the score of significant is lower than 0.05 (0.00 < 0.05). Besides, students faced several problems in learning grammar, such as are misuse tenses, misuse modal auxiliary, misuse nominal and verbal sentence, and pronoun. The reason students faced those problems can be caused by the student itself, lecturer and inadequate knowledge.